Preparation of Chicken Anemia Virus (CAV) Virus-Like Particles and Chicken Interleukin-12 for Vaccine Development Using a Baculovirus Expression System - Tseng, Ta-Yuan; Liu, Yee-Chen; Hsu, Yu-Chen; Chang, Poa-Chun; Hsieh, Ming-Kun; Shien, Jui-Hung; Ou, Shan-Chia (Pathogens (Basel), 2019)
Chicken infectious anemia (CIA) is a poultry disease that causes huge economic losses in the poultry industry worldwide. Commercially available CIA vaccines are derived from wild-type chicken anemia viruses (CAVs) by serial passage in cells or chicken embryos. However, these vaccinal viruses are not completely attenuated; therefore, they can be transmitted vertically and horizontally, and may induce clinical symptoms in young birds. In this study, we sought to eliminate these issues by developing a subunit vaccine exploiting the CAV structural proteins, engineering recombinant baculovirus-infected Spodoptera frugiperda (Sf9) cells that contained both the viral protein 1 (VP1) and VP2 of CAV. Moreover, we produced single-chain chicken interleukin-12 (chIL-12) in the same system, to serve as an adjuvant. The recombinant VP1 was recognized by chicken anti-CAV polyclonal antibodies in Western blotting and immunofluorescence assays, and the bioactivity of the recombinant chIL-12 was confirmed by stimulating interferon-γ (IFN-γ) secretion in chicken splenocytes. Furthermore, the ability of the recombinant VP1 to generate self-assembling virus-like particles (VLPs) was confirmed by transmission electron microscopy. Specific pathogen-free (SPF) chickens inoculated with VLPs and co-administered the recombinant chIL-12 induced high CAV-specific antibodies and cell-mediated immunity. Taken together, the VLPs produced by the baculovirus expression system have the potential to be a safe and effective CIA vaccine. Finally, we demonstrated the utility of recombinant chIL-12 as an adjuvant for poultry vaccine development.